\(A=1+2+2^2+...+2^{2018}\)
\(2A=2+2^3+2^4+...+2^{2019}\)
\(A=2A-A=1-2^{2019}\)
\(B-A=2^{2019}-\left(1-2^{2019}\right)\)
\(B-A=2^{2019}-1+2^{2019}\)
\(B-A=1\)
`#3107`
\(A=1+2+2^2+2^3+...+2^{2018}\) và \(B=2^{2019}\)
Ta có:
\(A=1+2+2^2+2^3+...+2^{2018}\)
\(2A=2+2^2+2^3+...+2^{2019}\)
\(2A-A=\left(2+2^2+2^3+...+2^{2019}\right)-\left(1+2+2^2+2^3+...+2^{2018}\right)\)
\(A=2+2^2+2^3+...+2^{2019}-1-2-2^2-2^3-...-2^{2018}\)
\(A=2^{2019}-1\)
Vậy, \(A=2^{2019}-1\)
Ta có:
\(B-A=2^{2019}-2^{2019}+1=1\)
Vậy, `B - A = 1.`
A = 1 + 2 + 22 + 23 + ... + 22018
2.A = 2 + 22 + 23 + 24 + ... + 22019
A = 22019 - 1
B - A = 22019 - (22019 - 1) = 1